PENGARUH METODE EKSPERIMEN TERHADAP PENGENALAN MITIGASI BENCANA BANJIR PADA ANAK USIA DINI - Ifkanaia Zullfriadi; Eka Cahya Maulidiyah; Kartika Rinakit Adhe; Yes Matheos Lasarus Malaikosa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of experimental methods on the introduction of flood disaster mitigation in children aged 5–6 years. The study used a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type. The research subjects were 30 children in group B at Aisyiyah Bustanul Athfal 14 Kindergarten Surabaya, consisting of 15 children in the experimental group (B3) and 15 children in the control group (B2). The experimental group was given treatment in the form of learning with a simple experimental method, while the control group used conventional learning through worksheets. Data collection was carried out through pre-tests and post-tests using flood disaster mitigation introduction instruments that included indicators of flood causes, self-rescue measures, and disaster risk reduction efforts. Data analysis used the Wilcoxon Signed Ranks Test and the Mann–Whitney U Test because the data were not normally distributed. The results showed a significant increase in the post-test scores of the experimental group compared to the control group. The Wilcoxon test showed a significant difference between the pre-test and post-test of the experimental group, while the Mann–Whitney test showed a significant difference between the experimental group and the control group in the post-test results. Based on these findings, it can be concluded that the experimental method has a significant and more effective influence on increasing awareness of flood disaster mitigation in children aged 5–6 years. This method provides concrete learning experiences that align with the characteristics of early childhood cognitive development.